Subterranean termite, Macrotermes, play important role on plant nutritive cycles through disintegration and decomposition of organic matter processes. In the other hand, subterranean termite can cause wooden damage in the nature and human dormitory as well. Therefore, Macrotermes are potential pest and need to be controlled. Effective pest-control of subterranean termite can be made when their species status and distribution are well known. This research is aimed to identify the status of spec - Niken SUBEKTI; Dedy DURYADI; Dodi NANDIKA; Surjono SURJOKUSUMO; Syaiful ANWAR (Departemen Hasil Hutan, IPB, 2008)
Subterranean termite, Macrotermes, play important role on plant nutritive cycles through disintegration and decomposition of organic matter processes. In the other hand, subterranean termite can cause wooden damage in the nature and human dormitory as well. Therefore, Macrotermes are potential pest and need to be controlled. Effective pest-control of subterranean termite can be made when their species status and distribution are well known. This research is aimed to identify the status of species and the dispersal of Macrotermes at their natural habitat in order to explore natural bio-resources richness and as an effort towards effective pest-control due to increasing risk of attack. Survey method was used termite samples were collected at four different locations which are defined by global positioning system (GPS). Nest classification is according to Meyer et al. (2003). The nest mapping is based on the elevations of their natural habitat in Gunung Halimun Salak National Park (900-1000 asl), and (600-700 asl), Yanlappa sanctuary (200-300 asl), and Ujung Kulon Nasional Park (0-100 asl). Phylogenetic relationships analysis showed that subterranean termite Macrotermes in the natural forest community are belongs to one big group Macrotermes gilvus Hagen. Based on nest size, the colony of Macrotermes can be classified into three different sizes: large, medium, and small nest. Large and medium nest can be found in large amount in Yanlappa sanctuary (15 and 23 colonies, respectively) and the majority of small nest occurred in Gunung Halimun Salak National Park at 900 asl (78 colonies). Temperature and humidity is the most environmental factor that can influence on termite and other factor is rain fall, soil structure, and plant vegetation. Keywords: Distribution, identify, Macrotermes gilvus Hagen, nest